Health itinerary-related survival of children under-five with severe malaria or bloodstream infection, DR Congo - Tack, Bieke; Vita, Daniel; Nketo, José; Wasolua, Naomie; Ndengila, Nathalie; Herssens, Natacha; Ntangu, Emmanuel; Kasidiko, Grace; Nkoji-Tunda, Gaëlle; Phoba, Marie-France; Im, Justin; Jeon, Hyon Jin; et al. (PLoS neglected tropical diseases, 2023)
Prompt appropriate treatment reduces mortality of severe febrile illness in sub-Saharan Africa. We studied the health itinerary of children under-five admitted to the hospital with severe febrile illness in a setting endemic for Plasmodium falciparum (Pf) malaria and invasive non-typhoidal Salmonella infections, identified delaying factors and assessed their associations with in-hospital death.